2019
DOI: 10.1264/jsme2.me19041
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Characterization of Bacterial Communities in Moss-Covered and Unvegetated Volcanic Deposits of Mount Merapi, Indonesia

Abstract: Microbial colonization, followed by succession, on newly exposed volcanic substrates represents the beginning of the development of an early ecosystem. During early succession, colonization by mosses or plants significantly alters the pioneer microbial community composition through the photosynthetic carbon input. To provide further insights into this process, we investigated the three-year-old volcanic deposits of Mount Merapi, Indonesia. Samples were collected from unvegetated (BRD) and moss-covered (BRUD) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 72 publications
(101 reference statements)
0
8
0
Order By: Relevance
“…(lady fern), Imperata cylindrica (cogon grass), and Anaphalis javanica (Javanese edelweiss). The TC and TN contents on the site were reported almost undetected [23].…”
Section: Sample Collection and Study Sites Informationmentioning
confidence: 94%
See 2 more Smart Citations
“…(lady fern), Imperata cylindrica (cogon grass), and Anaphalis javanica (Javanese edelweiss). The TC and TN contents on the site were reported almost undetected [23].…”
Section: Sample Collection and Study Sites Informationmentioning
confidence: 94%
“…Merapi, Special Region of Yogyakarta Province (07°34̍ 39̎ S, 110°26̍ 51̎ E, and 1,199 m.a.s.l.) [23]. The deposit sampled site (site BRU) was dominantly inhabited by pioneer moss namely Campylopus umbellatus and partly by Athyrium sp.…”
Section: Sample Collection and Study Sites Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…Fujimura et al, (2012 and 2016) revealed the role of early microbial communities in supporting pioneering plant colonization in unvegetated volcanic deposits, suggesting that the bacterial community structure transitioned from chemotrophs (autotrophs) to heterotrophs [ 2 , 5 ]. In addition, Guo et al (2014) and Lathifah et al (2019) reported that successional change in the early soil microbial community occurred with primary vegetation that developed on the newly placed volcanic deposits, in which the plant benefit groups are mainly affiliated with the orders Burkholderiales and Rhizobiales, which are significantly increased with the vegetation succession [ 6 , 7 ]. Guo et al (2021) further revealed that different plant benefit groups dominated the rhizosphere in different developmental phases on the recent Miyake-jima volcanic deposits, i.e., Paraburkholderia and Trinickia represented the major plant-beneficial groups in the early colonization phase, whereas Rhizobiales and Arthrobacter increased in the later colonization phase [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on developing volcanic ash soils have so far concentrated on chemical characterisation of the ash soils 4 7 or description of bacterial communities using only 16S rRNA gene sequencing 8 11 . There have been few studies of the functional aspects of the biota of developing ash soils.…”
Section: Introductionmentioning
confidence: 99%